
By: geniuskids (offline) Monday, September 09 2013 @ 03:41 AM CDT (Read 849 times)



geniuskids 
Hi there, I am quite weak on such average question. Pls help me!
Thank You

Active Member
Registered: 11/12/11 Posts: 169





By: jo sarah (offline) Monday, September 09 2013 @ 04:16 AM CDT



jo sarah 
Let the no. of tumblers bought be 1u. at first.
Then, he paid. $11u at first.
When he bought another at $37, the total sum of money = $( 11u + 37 ),
Which is equal to ( 1u + 1 ) x $ 13 = $ (13u + 13 )
So, 13u + 13 = 11u + 37
Therefore, 2u = 24
giving, 1u = 12
That is, he bought 12 tumblers.
Cheerio!

Regular Member
Registered: 03/20/12 Posts: 111





By: jo sarah (offline) Monday, September 09 2013 @ 04:16 AM CDT



jo sarah 
Let the no. of tumblers bought be 1u. at first.
Then, he paid. $11u at first.
When he bought another at $37, the total sum of money = $( 11u + 37 ),
Which is equal to ( 1u + 1 ) x $ 13 = $ (13u + 13 )
So, 13u + 13 = 11u + 37
Therefore, 2u = 24
giving, 1u = 12
That is, he bought 12 tumblers.
Cheerio!

Regular Member
Registered: 03/20/12 Posts: 111





By: 555 (offline) Wednesday, September 11 2013 @ 04:19 AM CDT



555 

Newbie
Registered: 08/25/13 Posts: 5





By: geniuskids (offline) Wednesday, September 11 2013 @ 09:59 AM CDT



geniuskids 
Hi Jo_sarah, Thanks, managed to solve it!

Active Member
Registered: 11/12/11 Posts: 169



